2014
DOI: 10.1111/cla.12100
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and historical biogeography of the cocosoid palms (Arecaceae, Arecoideae, Cocoseae) inferred from sequences of six WRKY gene family loci

Abstract: Arecaceae tribe Cocoseae is the most economically important tribe of palms, including both coconut and African oil palm. It is mostly represented in the Neotropics, with one and two genera endemic to South Africa and Madagascar, respectively. Using primers for six single copy WRKY gene family loci, we amplified DNA from 96 samples representing all genera of the palm tribe Cocoseae as well as outgroup tribes Reinhardtieae and Roystoneae. We compared parsimony (MP), maximum likelihood (ML), and Bayesian (B) anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 141 publications
(265 reference statements)
5
66
0
4
Order By: Relevance
“…The uplift of the Andes and the bridging of the Panamanian Isthmus are two geological events that have been suggested to have had a profound impact on patterns of Neotropical plant diversification (Antonelli, Nylander, Persson, & Sanmartin, 2009;Burnham & Graham, 1999;Gentry, 1982aGentry, , 1982bHughes & Eastwood, 2006;Hughes, Pennington, & Antonelli, 2013;Knapp & Mallet, 2003;Meerow et al, 2014;Richardson, Pennington, Pennington, & Hollingsworth, 2001;Roncal, Kahn, Millan, Couvreur, & Pintaud, 2013). The area that Colombia occupies in north-western South America is one of the most geologically interesting places on Earth, with it being the point of contact between Laurasia and Gondwanaland, as the Panama Isthmus closed and with the rise of the Andes occurring more recently there than further south.…”
Section: What We Know About the Uplift Of The Andesmentioning
confidence: 99%
“…The uplift of the Andes and the bridging of the Panamanian Isthmus are two geological events that have been suggested to have had a profound impact on patterns of Neotropical plant diversification (Antonelli, Nylander, Persson, & Sanmartin, 2009;Burnham & Graham, 1999;Gentry, 1982aGentry, , 1982bHughes & Eastwood, 2006;Hughes, Pennington, & Antonelli, 2013;Knapp & Mallet, 2003;Meerow et al, 2014;Richardson, Pennington, Pennington, & Hollingsworth, 2001;Roncal, Kahn, Millan, Couvreur, & Pintaud, 2013). The area that Colombia occupies in north-western South America is one of the most geologically interesting places on Earth, with it being the point of contact between Laurasia and Gondwanaland, as the Panama Isthmus closed and with the rise of the Andes occurring more recently there than further south.…”
Section: What We Know About the Uplift Of The Andesmentioning
confidence: 99%
“…A reconstruction of phylogenetic relationships within Attaleinae based on nuclear WRKY genes, conversely, resolved Voanioala and Jubaeopsis with strong support as sister genera and together with Beccariophoenix as distinct sister clade to the American genera [Meerow et al, 2009[Meerow et al, , 2015. This relationship of clades clearly suggests a common polyploid ancestor of Voanioala and Jubaeopsis .…”
Section: Polyploidy and Biogeographymentioning
confidence: 94%
“…Among almost 100 weevils known from Burmese amber to date, and many thousands of Coleoptera, no additional specimens of Curculionidae have come to light, throwing further doubt on the origin of the two members of Curculionidae described thus far from Burmese amber. [62,63]. Based on a review of the literature and extensive fieldwork, he found that the most abundant weevils visiting flowers of Syagrus coronata (Mart.)…”
Section: The Burmese Amber Weevil Fauna (Rolf Oberprieler)mentioning
confidence: 99%